Polar policy making: Two ethnographic accounts of Polar field scientists interacting with Polar governance and policy. (September 2019) - Ferguson, Laura
This review article discusses the recent publications Studying Arctic Fields by Richard C Powell and The Technocratic Antarctic by Jessica O'Reilly. Both books are ethnographic accounts of scientists working in the Polar Regions that analyse interactions at the science–policy interface. Studying Arctic Fields is a detailed story of Canada's Resolute research station, based on immersive ethnographic observation and communicated through an engaging narrative of colourful stories from Powell's two summers among the scientists and support staff there. The Technocratic Antarctic treads new ground in its examination of Antarctic social science, presenting the findings of a wide-ranging and thorough research project that engages with the themes of territory, security, processes, practice, problems and science communication. Both publications make valuable contributions to Polar social science and will also appeal to many beyond this.